Dendrites in Zn‐Based Batteries. Issue 48 (26th October 2020) - Yang, Qi; Li, Qing; Liu, Zhuoxin; Wang, Donghong; Guo, Ying; Li, Xinliang; Tang, Yongchao; Li, Hongfei; Dong, Binbin; Zhi, Chunyi
Abstract: Aqueous Zn batteries that provide a synergistic integration of absolute safety and high energy density have been considered as highly promising energy‐storage systems for powering electronics. Despite the rapid progress made in developing high‐performance cathodes and electrolytes, the underestimated but non‐negligible dendrites of Zn anode have been observed to shorten battery lifespan. Herein, this dendrite issue in Zn anodes, with regard to fundamentals, protection strategies, characterization techniques, and theoretical simulations, is systematically discussed. An overall comparison between the Zn dendrite and its Li and Al counterparts, to highlight their differences in both origin and topology, is given. Subsequently, in‐depth clarifications of the specific influence factors of Zn dendrites, including the accumulation effect and the cathode loading mass (a distinct factor for laboratory studies and practical applications) are presented. Recent advances in Zn dendrite protection are then comprehensively summarized and categorized to generate an overview of respective superiorities and limitations of various strategies. Accordingly, theoretical computations and advanced characterization approaches are introduced as mechanism guidelines and measurement criteria for dendrite suppression, respectively. The concluding section emphasizes future challenges in addressing the Zn dendrite issue and potential approaches to further promoting the lifespan of Zn batteries. Abstract : Zinc‐based batteries demonstrate both intrinsic safety and high energy density compared with other metal batteries. Nevertheless, zinc‐dendrite issues such as special morphology and nucleation require unique protections, which develop rapidly and need further improvement. The remaining challenges are discussed and the future directions, i.e., dynamic contact, atomic‐level ionic flow mediation, dendrite protection under high depth of discharge, etc., are proposed.